Spelling in context : strategies for teachers and learners - Peters, Margaret L.; Smith, Brigid (Windsor, Berks. : NFER-NELSON, 1993)
Spelling: its place in writing. The process of writing. Spelling: classroom management and school policies. The development of spelling. Diagnosing specific spelling difficulties...
Keywords: English language; Language teaching; Orthography and spelling; Remediial teaching; Spelling disability; English language -- Orthography and spelling -- Study and teaching (Primary); Spelling disability; English language -- Remedial teaching